KRITIK TERHADAP PEMIKIRAN TASAWUF AL-RANIRI - Syaifan Nur (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2013)
Al-Raniri is often positioned by some scholars as “superior” fi gure, which is contrasted to Hamzah Fansuri and Syamsuddin Sumaterani, and that is why they predicate him as one of pioneer of Islamic reformer in MalayIndonesian archipelago. Anti wujūdiyyah Sufi sm campaign by al-Raniri quite successful to some extent to amputate the rate of development of philosophical Sufism was brought by Fansuri and Sumaterani in the one hand, and strike off the nature of moral Sufi sm in the other, redeemed by bloodshed. This article discussed the “superiority” of al-Raniri’s thought of Sufism, viewed from a broader spectrum, either in relation to problems of faith or theology and politics surrounding the circumstance of his time.